The intended and unintended consequences of financial-market regulations: A general equilibrium analysis - Adrian Buss; Bernard Dumas; Raman Uppal; Grigory Vilkov (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
In a production economy with trade in financial markets motivated by the desire to share labor-income risk and to speculate, we show that speculation increases volatility of asset returns and investment growth, increases the equity risk premium, and reduces welfare. Regulatory measures, such as constraints on stock positions, borrowing constraints, and the Tobin tax have similar effects on financial and macroeconomic variables. Borrowing limits and a financial transaction tax improve welfare because they substantially reduce speculative trading without impairing excessively risk-sharing trades.
urn:nbn:de:hebis:30:3-393016
Keywords: G01; G18; G12; E44; 330; Tobin tax; borrowing constraints; short-sale constraints; stock market volatility; incomplete markets; differences of opinion